A thematic review on accounting conservatism and corporate tax planning / Noor Emilina Mohd Nasir ... [et al.] - Mohd Nasir, Noor Emilina; Kamarudin, Siti Nurhazwani; Rashid, Norfadzilah; Yaacob, Najihah Marha (Research Management Institute (RMI), 2023)
Corporate tax planning as a strategy for minimising tax liability by companies has been frequently discussed. Many discoveries have been established by previous academics regarding the determinants of corporate tax planning. However, accounting conservatism is infrequently discussed in the context of corporate tax planning. Accounting conservatism is the accounting principle that businesses employ when preparing financial statements. Since tax reporting is dependent on audited financial statements, the choice of accounting principle impacts tax strategy. Thus, the main purpose of this paper is to examine the accounting conservatism patterns discussed by previous researchers. Using ATLAS.ti 22, the results report a thematic review analysis of the literature on accounting conservatism and taxation from 2000 to 2022. Keyword searches yielded 123 and 124 articles, respectively, in the Web of Science and Scopus databases. Nonetheless, only 22 articles were included for the analysis after being filtered based on inclusion and exclusion criteria. The analysis revealed a few studies that analysed the connection between accounting conservatism and corporate tax preparation. This finding highlights the significance of further research into the impact of accounting conservatism on the implementation of tax planning strategies.